Pendampingan Manajemen Kapasitas Produksi Pada Industri Tas - Marie, Iveline Anne; Sari, Emelia; Farhan, Ahmad; Habyba, Anik Nur; Moengin, Parwadi; Witonohadi, Amal; Suryana, Yunita Friscilia; Nabila, Shadrina Putri; Ilham, Ahmad (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
PT TIJ is a women's bag company located in Cilodong - Depok which has grown with family management. Companies need to share knowledge regarding plans to increase bag production capacity to meet customer demand. This Community Service Activity (CSA) is a continuation of outreach and mentoring activities. Based on the evaluation results of previous PkM activities and the results of discussions with the company during mentoring, it can be seen that the production line experiencing production capacity problems is the bag assembly line. The company needs further activities to achieve the company's production targets which continue to increase both in variety and production capacity. Industrial partners are expected to have an understanding of the concept of production capacity and its calculations as well as strategic plans to increase production capacity following increasing demand. PkM activities aim to provide counseling and assistance regarding calculating production capacity and strategies for increasing production capacity on bag assembly lines. The implementation of PkM has been carried out well and has been confirmed to be able to improve company performance through improving production capacity management. Furthermore, PkM is expected to focus on improving the company's human resources.